Управление в высшей школе: опыт, тенденции, перспективы: аналитический доклад - Филиппов В. М.; Агранович Б. Л. Борис Львович; Арсеньев Д. Г; Аржанова И. В; Васильев В. Н.; Востриков А. С.; Грудзинский А. О.; Жураковский В. М.; Карнаухов Н. Н.; Клюев А. К.; Кличко Т. Л.; Князев Е. А.; et al. (Москва, Логос, 2005)
В фонде НТБ ТПУ отсутствует